Alat Ukur Tinggi dan Berat Badan Untuk Menentukan Status Gizi Pada Anak Berbasis Arduino - Fitriani, Fuji, Umi Fadililah, S.T, M.Eng (2017)
Early childhood is the individuals who are at the age of 0-5 years. At this age is the golden age, where the condition of children experience physical and psychological development is rapid. It terntu influenced by the physical and psychological health in children. In fact, not a few children who have health problems, such as lack of fulfillment of nutrition in children. The purpose of this study was to determine the nutrition in children by measuring the height and weight by using a measuring instrument based Arduino. This instrument is controlled by arduino using ultrasonic sensors as medium height gauge and load cell to determine the child's weight. Height and weight measurement is done by sitting, to measure the height was limited to high-fathom alone while the weight sensor using a load cell. The incoming data will be processed by a microcontroller arduino displayed via the LCD screen. The purpose of this tool is to provide the latest innovations in measuring height and weight to determine the nutritional status of children.